ANALISA LAJU KOROSI PADA PIPA HASIL PEMOTONGAN ALAT PEMOTONG BENDA SILINDRIS BERBASIS OXY-ACETYLENE TERHADAP AIR LAUT - Aprilianto, Mochammad Ismail Bagus; Sakti, Arya Mahendra (Jurnal Rekayasa Mesin, 2022)
The type of sea transportation in Indonesia is the ship, because the ship is an important means in the activities of relations between people from one island to another. Ships that have a Water Ballast Tank mounted on the side of the ship in order to make the ship balanced. In general, Water Ballast Tanks are installed in two different places, to maintain the balance of the ship by removing water through the side of the ship. Pipes as a means of disposing of sea water in the Ballast Tank. In the manufacture of Water Ballast Tank pipes, it is necessary to require a cutting process and appropriate material selection. The research on analyzing the corrosion rate on the pipe cutting results from oxy-acetylene-based cylindrical cutting tools against seawater objective to determine the appropriate materials.This research starts from formulating the problem researched by conducting a survey and searching for literature as a bibliography. The data analysis method used in this research is quantitative and qualitative descriptive statistics. Quantitative analysis technique is carried out by examining the data obtained from the experiment, and the results are made in tabular format and in the form of quantitative data displayed in graphic format.The sequence of the corrosion rate analysis process starts from cutting with an oxy-acetylene-based cylindrical object cutting tool, then cleaning from the crust, after that the initial weight and immersion process is carried out after lifting and weighing the final weight. The results of this corrosion rate analysis starting from cutting with oxy-acetylene-based cylindrical cutting tools, the results of the statement are that the farther the cutting distance on the galvanized material, the greater the corrosion rate and the closer the cutting distance on steel material, the greater the corrosion rate and on iron material. it can be concluded that the 7 mm cutting distance the corrosion rate is smaller than the 5 mm and 10 mm cutting distances.